2019
DOI: 10.1029/2018jd029347
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Changes in Land‐Sea Thermal Contrast Across China's Coastal Zone in a Warming Climate

Abstract: Coastal areas are important sites of environmental and socioeconomic activities and are significantly influenced by climate change. Here we analyzed the current and future responses of spatiotemporal characteristics of land‐sea thermal contrast (LSTC) along China's coastal zone to global warming. Using the European Centre for Medium‐Range Weather Forecasts Re‐Analysis (ERA)‐Interim and 18 Coupled Model Intercomparison Project 5 models, we find that the rate of global warming significantly influenced the LSTC i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…The wind stress is calculated using the formula of Large and Pond (1982) with some modification from Trenberth et al (1990) (Dittmer, 1977;Schacher et al, 1981) (Supporting Information S1). The ERAI data uses the 4D-Var analysis technique (Li et al, 2016) and its net surface heat flux shows superior performance over other products for the western Pacific region (Song & Yu, 2013;Song et al, 2015;Yao et al, 2019;Zhang et al, 2016). Before the calculation of wind stress, we apply a creeping sea-fill methodology to the ERAI data to correct the land contamination near land-sea boundaries following Kara et al (2007).…”
Section: Atmospheric Forcing and Bathymetry Datamentioning
confidence: 99%
“…The wind stress is calculated using the formula of Large and Pond (1982) with some modification from Trenberth et al (1990) (Dittmer, 1977;Schacher et al, 1981) (Supporting Information S1). The ERAI data uses the 4D-Var analysis technique (Li et al, 2016) and its net surface heat flux shows superior performance over other products for the western Pacific region (Song & Yu, 2013;Song et al, 2015;Yao et al, 2019;Zhang et al, 2016). Before the calculation of wind stress, we apply a creeping sea-fill methodology to the ERAI data to correct the land contamination near land-sea boundaries following Kara et al (2007).…”
Section: Atmospheric Forcing and Bathymetry Datamentioning
confidence: 99%
“…In coastal China from 1986 to 2015, the maximum 1-day and maximum 5-day precipitation increased at rates of 0.25 mm y −1 and 0.49 mm y −1 , respectively, although the trend was not significant [14,15]. Besides, the temperature was generally increased with the background of global warming [14,15]. The terrain in the study area is complex and diverse, and there are plains, plateaus, and hills.…”
Section: Study Areamentioning
confidence: 91%
“…This might enhance plant respiration in nighttime, while inhibit leaf photosynthesis in daytime, reducing accumulation of dry matter. Second, Xu et al [14] and Wang et al [15] reported that the extreme precipitation in coastal China showed an increased trend in recent decades, which may inhibit vegetation growth. More importantly, some studies have shown that in metropolitan areas, the combined effects of extreme climate and negative human activities amplify the effects of both on vegetation [77,78].…”
Section: Effectiveness Of Residual Trend Analysis Methods To Separate...mentioning
confidence: 99%
See 2 more Smart Citations